An Anatomic Study of the Keyhole Supra-Tentorium to Infra-Tentorium Endoscope Approach. Issue 6 (September 2019) - Ye, Pin; Sun, Tao; Li, Zongfang; Yang, Zhihong; Li, Guoping; Chen, Shaochun
Abstract : Abstract: To provide anatomic basis for the retrosigmoid supra-tentorium to infra-tentorium keyhole approach and to explore the feasibility, 60 skulls were observed and measured to demonstrate the position relations among related bony landmarks, 12 cadaveric heads were dissected and measured for localization of the keyhole and the incision through tentorium. For giving the angle and depth for endoscopic approach, 40 adult volunteers were performed head MRI scan and the pictures were measured and analyzed. The surface projection of sigmoid and transverse sinus can be positioned by mastoidale, external occipital protuberance, and anterior end of parietomastoid suture (AEPMS) on body. There is a safe trigone of cerebellar tentorium (STCT) among inner edge of upper curve of sigmoid sinus, entrance of tentorial sinus/vein and midpoint of posterior edge of temporal arcuate eminence. 15 mm superior to the midpoint between asterion and AEPMS can be recognized as the central point of the keyhole. Magnetic resonance imaging pictures show there is potential subarachnoid space for endoscopic approach from the indicated keyhole to pontocerebellar trigone. This study demonstrated endoscopy can arrive at pontocerebellar trigone through the STCT and the keyhole supra-tentorium to infra-tentorium endoscope approach is feasible in anatomy and will contribute to excise lesions involving both supra- and infra-tentorial structures. Abstract : Supplemental Digital Content is available in the text